â€˜Praatâ€™ Sebagai Media Pembelajaran Ton Bahasa Mandarin Pada Tuturan Deklaratif Bahasa Mandarin: Fonetik Akustik - Siregar, Sheyla Silvia; Siregar, Sheyra Silvia (Titian: Jurnal Ilmu Humaniora, 2023)
The learning process is basically a communication process through interaction between teachers and students. In the communication process the message is conveyed by the communicator (teacher) to the recipient of the message or the so-called communicant (student). The use of digital media as learning has undergone significant development. The presence of digital media provides a variety of educational innovations, where conventional learning that is rigid and monotonous will be replaced by learning using digital media which is considered more practical, flexible, not limited by space and time. Learning media with digital technology cannot be denied as a sophisticated media or meet the novelty that is usually familiar to students. 'Praat' is one type of software that helps researchers to analyze sound. 'Praat' as one of the current innovations of foreign language learning media, especially Mandarin. This study is entitled 'This study aims to describe the frequency of interrogative speech in Mandarin native speakers and learners of basic Chinese, describe the interrogative utterances of native speakers and learners of basic Mandarin and describe the patterns of interrogative speech patterns in Mandarin native speakers and learners of basic Chinese. Data retrieval was done by recording the voice of interrogative Chinese speech by native speakers and basic Chinese learners. Respondents were then divided into two based on gender and ethnicity. The results of the recorded voice ton patterns that have been analyzed are then compared with native speakers. The students taken are foreign students of basic-intermediate Mandarin (Zhongji Shang). The theory used in this study is the ton theory of Mandarin by 'Chao Yuan Ren' and 'Praat'. Abstrak Proses pembelajaran pada dasarnya merupakan proses komunikasi melalui interaksi antara guru dengan murid. Dalam proses komunikasi pesan disampaikan olek pihak komunikator (pengajar) kepada penerima pesan atau yang disebut komunikan (peserta didik). Pemanfaatan media digital sebagai pembelajaran sudah mengalami pengembangan yang signifikan. Hadirnya media digital ini memberikan beragam inovasi pendidikan, dimana pembelajaran kovensional yang kaku dan monoton akan digantikan dengan pembelajaran mengunakan media digital yang dianggap lebih praktis, fleksibel, tidak dibatasi oleh ruang dan waktu. Media pembelajaran dengan teknologi digital tidak dapat dipungkiri sebagai media yang canggih atau memenuhi kebaruan (novelty) yang biasanya akrab dengan peserta didik. â€˜Praatâ€™ merupakan salah satu jenis perangkat lunak yang membantu peneliti untuk menganalisis suara. â€˜Praatâ€™ sebagai salah satu inovasi masa kini media pembelajaran Bahasa asing khususnya Bahasa Mandarin. Penelitian ini berjudul â€˜Penelitian ini bertujuan mendeskripsikan frekuensi tuturan interogatif bahasa Mandarin penutur asli dan pemelajar bahasa Mandarin dasar, mendeskripsikan ton tuturan interogatif penutur asli dan pemelajar bahasa Mandarin dasar dan mendeskripsikan pola ton tuturan interogatif dalam bahasa Mandarin penutur asli dengan pembelajar bahasa Mandarin dasar. Pengambilan data dilakukan dengan cara merekam suara tuturan interogatif bahasa Mandarin oleh penutur asli dan pemelajar bahasa Mandarin dasar. Responden kemudian dibagi menjadi dua berdasarkan jenis kelamin danÂ  suku. Hasil rekaman pola ton suara yang telah dianalisis kemudian dibandingkan dengan penutur asli. Pemelajar yang diambil adalah pemelajar asing bahasa Mandarin dasar-menengah (Zhongji Shang). Teori yang digunakan dalampenelitian ini adalah teori ton bahasa Mandarin oleh â€˜Chao Yuan Renâ€ dan â€˜Praatâ€™.